Healthcare sensor networks : challenges toward practical implementation - Lai, Daniel T. H.; Begg, Rezaul; Palaniswami, Marimuthu (Boca Raton : CRC Press/Taylor & Francis Group, 2012)
Includes bibliographical references and index.